2017
DOI: 10.1021/acs.chemmater.7b01936
|View full text |Cite
|
Sign up to set email alerts
|

Protein-Imprinted Polymers: The Shape of Things to Come?

Abstract: The potential to develop materials with antibody-like molecular recognition properties has helped sustain interest in protein-imprinted polymers over the past several decades. Unfortunately, despite persistent research, the field of noncovalent protein imprinting has seen limited success in terms of achieving materials with high selectivity and high affinity. In this Perspective, important yet sometimes overlooked aspects of the imprinting and binding processes are reviewed to help understand why there has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
90
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 121 publications
(91 citation statements)
references
References 69 publications
1
90
0
Order By: Relevance
“…Until now, template molecules have typically comprised small inorganic, organic or organic–inorganic species and the use of proteins as templating agents is yet to be reported. In polymer chemistry, proteins have been applied as removable templates to fabricate molecularly imprinted polymers (MIPs), which can be used for protein recognition . These results inspired us to explore if proteins, especially bioactive enzymes, can indeed be used as templates to form new ZMOFs which can inherit the function of proteins (for example, catalysis, recognition, and sensing).…”
Section: Methodsmentioning
confidence: 99%
“…Until now, template molecules have typically comprised small inorganic, organic or organic–inorganic species and the use of proteins as templating agents is yet to be reported. In polymer chemistry, proteins have been applied as removable templates to fabricate molecularly imprinted polymers (MIPs), which can be used for protein recognition . These results inspired us to explore if proteins, especially bioactive enzymes, can indeed be used as templates to form new ZMOFs which can inherit the function of proteins (for example, catalysis, recognition, and sensing).…”
Section: Methodsmentioning
confidence: 99%
“…[138] While there has been research to develop synthetic alternatives to antibodies, such as protein-imprinted polymers, several studies have found that these materials may not offer any significant advantages over their nonimprinted counterparts. [139,140] Ultimately, the choice of recognition element is dependent on the desired biomarker and fluid for detection; protein-specific antibodies and aptamers have been found to work best for proteins with lower concentrations or in protein-rich biofluids and synthetic or less specific agents are able to offer lower cost alternatives for biomarkers that are major components of the target sample.…”
Section: Design Considerations In Biomaterials Systems For Disease Trementioning
confidence: 99%
“…To facilitate the formation of functional tissues, advanced biomaterials with controlled physical, chemical, biological, and electrical properties should be designed . Hydrogels are one of the few biomaterials that possess properties required for tissue engineering applications .…”
Section: Introductionmentioning
confidence: 99%